Existence of Subharmonic Periodic Solutions to a Class of Second-Order Non-Autonomous Neutral Functional Differential Equations - Xiao-Bao Shu; Yongzeng Lai; Fei Xu (Abstract and Applied Analysis)
By introducing subdifferentiability of lower semicontinuous convex function φ(x(t),x(t−τ)) and its conjugate function, as well as critical point theory and operator equation theory, we obtain the existence of multiple subharmonic periodic solutions to the following second-order nonlinear nonautonomous neutral nonlinear functional differential equation x″(t)+x″(t−2τ)+f(t,x(t),x(t−τ),x(t−2τ))=0, x(0)=0.